2015
DOI: 10.5334/ijic.1527
|View full text |Cite
|
Sign up to set email alerts
|

The performance of integrated health care networks in continuity of care: a qualitative multiple case study of COPD patients

Abstract: Background: Integrated health care networks (IHN) are promoted in numerous countries as a response to fragmented care delivery by providing a coordinated continuum of services to a defined population. However, evidence on their effectiveness and outcome is scarce, particularly considering continuity across levels of care; that is the patient's experience of connected and coherent care received from professionals of the different care levels over time. The objective was to analyse the chronic obstructive pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 44 publications
6
36
0
3
Order By: Relevance
“…Conversely, loss of identity,17 poor continuity of care from health professionals, poor communication between members of the healthcare team,38 exclusion from social networks and socioeconomic disadvantage are equally recognised as key barriers 39. These influences are associated with reduced coping ability, decreased help seeking,40 the need to continually repeat medical history and are barriers to develop trusting relationships with health professionals 41. In comparison with other qualitative Australian studies into the patient’s experience of COPD, beneficial impacts were reported when patients felt supported by community members and health professionals,33 42 43 connected to people and nature,42 felt a strong sense of community43 and felt listened to by health professionals 44…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, loss of identity,17 poor continuity of care from health professionals, poor communication between members of the healthcare team,38 exclusion from social networks and socioeconomic disadvantage are equally recognised as key barriers 39. These influences are associated with reduced coping ability, decreased help seeking,40 the need to continually repeat medical history and are barriers to develop trusting relationships with health professionals 41. In comparison with other qualitative Australian studies into the patient’s experience of COPD, beneficial impacts were reported when patients felt supported by community members and health professionals,33 42 43 connected to people and nature,42 felt a strong sense of community43 and felt listened to by health professionals 44…”
Section: Discussionmentioning
confidence: 99%
“…A conformação em RAS, tendência internacional, visa a superar o cuidado fragmentado, os custos elevados, com expectativa de maior eficiência ao sistema 20,21,22 . Quando baseada em território, a RAS reduz as desigualdades locorregionais e as iniquidades de acesso 9 .…”
Section: Discussionunclassified
“…Integrated care has system, organizational and clinical levels [20][21][22]. The system level includes both vertical and horizontal integration.…”
Section: Integrated Carementioning
confidence: 99%
“…Although, there is certainly overlap with self management, the focus of care coordination on organizational aspects of patient care [36] gives it a different spin. Continuity of care, a goal of care coordination, has three aspects: 1) Continuity of clinical management; 2) Continuity of information; and 3) Relational continuity [22]. Like self-management, care coordination can be considered a component of integrated care.…”
Section: Care Coordinationmentioning
confidence: 99%